Prenatal Drugs and Their Effects on the Developing Brain: Insights From Three-Dimensional Human Organoids - Stankovic, Isidora N.; Colak, Dilek (Frontiers in Neuroscience, 2022)
Decades of research have unequivocally demonstrated that fetal exposure to both recreational and prescription drugs in utero negatively impacts the developing brain. More recently, the application of cutting-edge techniques in neurodevelopmental research has attempted to identify how the fetal brain responds to specific environmental stimuli. Meanwhile, human fetal brain studies still encounter ethical considerations and technical limitations in tissue collection. Human-induced pluripotent stem cell (iPSC)-derived brain organoid technology has emerged as a powerful alternative to examine fetal neurobiology. In fact, human 3D organoid tissues recapitulate cerebral development during the first trimester of pregnancy. In this review, we aim to provide a comprehensive summary of fetal brain metabolic studies related to drug abuse in animal and human models. Additionally, we will discuss the current challenges and prospects of using brain organoids for large-scale metabolomics. Incorporating cutting-edge techniques in human brain organoids may lead to uncovering novel molecular and cellular targets relevant to neurodevelopment, direct novel therapeutic approaches and raise new exciting questions.